BOOKBINDING: A RELIC OR A VALUE? - KOLPAKOVAITĖ, AURIKA (Knygotyra, 2014)
Vilniaus universiteto Knygotyrosir dokumentotyros institutasUniversiteto g. 3, Lt-01513 Vilnius, LietuvaEl. paštas: aurika.kolpakovaite@gmail.com